Calculations of the geodesic curvature of a magnetic line for the URAGAN-2M torsatron with taking into account the influence of the current-feeds and detachable joints of the helical winding - Nemov, V.V.; Kalyuzhnyj, V.N.; Kasilov, S.V.; Lesnyakov, G.G.; Besedi, N.T. (Вопросы атомной науки и техники, 2006)
The database for the coils of the U-2M magnetic system which wasformerly used in computations of magnetic surfaces with taking
into account the influence of the current-feeds and detachable joints of the helical winding is transformed to a new form which is
valid for the already existing Biot-Savart code for computations of the magnetic field strength, and its spatial derivatives. With this
code, using the transformed database, computations are performed for the geodesic curvature of the magnetic field lines for few
configurations of U-2M. These computations are considered as a preliminary work for future transport computations. База данных для проводников магнитной системы торсатрона У-2М, использовавшаяся ранее для вычисления магнитных
поверхностей с учетом влияния токоподводов и токоразъемов, преобразована к новому виду, который может
использоваться в уже существующем коде на основе закона Био-Савара для вычисления напряженности магнитного поля и
ее пространственных производных. С использованием этого кода и преобразованной базы данных выполнены расчеты
геодезической кривизны силовых магнитных линий для нескольких конфигураций У-2М. Эти расчеты являются
предварительным этапом последующих расчетов процессов переноса. База даних для провідників магнітної системи торсатрона У-2М, що використовувалася раніше для розрахунків магнітних
поверхонь із урахуванням впливу струмопідводів та струморознімань, перетворена до нового виду, який може
використовуватися у вже існуючому коді на основі закону Біо-Савара для розрахунків напруженості магнітного поля та її
просторових похідних. З використанням цього коду та перетвореної бази даних виконано розрахунки геодезичної кривизни
силових магнітних ліній для декількох конфігурацій У-2М. Ці розрахунки є попереднім етапом наступних розрахунків
процесів переносу.